Haematological Disease - Estcourt, L; Stanworth, S; Stanworth, S; Murphy, M; Murphy, M (John Wiley and Sons, 2013)
Patients with haematological diseases are major users of blood components. This chapter focuses on bone marrow failure syndromes and stem cell transplantation, in addition to haematological malignancies. The transfusion support of patients with haematological disease may be complex and includes the management of ABO mismatched stem cell transplants, the investigation and management of patients who become refractory to platelets and the use of irradiated and CMV-safe blood components. This edition first published 2013 © 2001, 2005, 2009, 2013 John Wiley and Sons Ltd.